Education, Republican Right and Duty - Bigarella, Nadia Bigarella; Lewandowski, Alessandro Gomes (Série-Estudos, 2016)
This article is part of a Masters research in progress and has as its object the Brazilian State facing the right to education. By means of a documental research, on the basis of the Federal Constitution of 1988, the Law of Guidelines and Bases 9.394/1996 and other documents aimed to discuss how this right has materialized throughout history. The results show that the right to education is a fundamental dimension of citizenship, which is related to a conception of the State and their form of government. This right extends beyond the idea of set of rules, guidelines and actions, because it is linked to the commitment of thinking a model other society with a division of wealth more fairly